Rumah Internet Pelajar (RUMINJAR) As Learning Facility During Covid19 For Students In Sopotinjak Village, Batang Natal - Nainggolan, Elizon; indria, friska; damanik, anggita; lidya, hesty; anggina, putri (Jurnal Nauli, 2021)
The spread of the Covid-19 virus that has swept across the world has changed various aspects of human life, one of which is changes in the learning process in the educational environment, from elementary, junior high, high school, to university levels. Learning that initially relied on face-to-face lectures shifted to online learning. Not many students and students have to make an effort to keep up with the online learning process. Therefore the purpose of this research is to find out the problems / obstacles that students and students often face during online learning and to find out the role of Ruminjar in the effectiveness of online learning in Sopotinjak Village. This study uses a library research method where all data is taken based on journals, books, and direct observation.